Mediated roles of oxidative stress and kidney function to leukocyte telomere length and prognosis in chronic kidney disease - Jiahong Yi; Chang Jiang; Liangping Xia (Renal Failure)
Background Few studies have focused on the correlation between leukocyte telomere length (LTL) and cancer-related mortality or identified potential factors that mediate the relationship between LTL and mortality among chronic kidney disease (CKD) patients. Our study aimed to explore the associations between LTL and all-cause and cause-specific mortality and to identify the underlying mediators.Methods CKD patients were obtained from the National Health and Nutrition Examination Survey (NHANES) 1999–2002. Cox regression analysis and restricted cubic spline analysis were used to explore the associations between LTL and all-cause or specific-cause mortality and their nonlinear connections. Stratified analyses were executed to assess the relationships among the different subgroups. The latent mediated factors were confirmed using mediation analysis. Sensitivity analyses were used to evaluate the robustness of our findings.Results Longer LTL associated with the lower risk of all-cause mortality, cardiovascular disease (CVD) and cancer-related mortality, and U-shaped relationships were detected. Patients younger than 65 years with greater LTL or who had hypertension had better prognoses. Age and history of hypertension were associated with LTL and overall mortality. In addition, estimated glomerular filtration rate (eGFR), albumin, and total bilirubin mediated the association, and the proportions of indirect effects were 7.81%, 3.77%, and 2.50%, respectively. Six sensitivity analyses confirmed the robustness of our findings.Conclusions This study revealed that LTL was a protective factor for survival among patients with CKD and emphasized the mediating roles of oxidative stress and kidney function.